Workload increases nurses' quiet quitting, turnover intention, and job burnout: evidence from Greece - Petros Galanis; Ioannis Moisoglou; Aglaia Katsiroumpa; Parisis Gallos; Maria Kalogeropoulou; Evangelia Meimeti; Irene Vraka (AIMS Public Health)
IntroductionHigh workloads among nurses affect critical workplace outcomes, such as turnover intention, job burnout, and job satisfaction. However, there are no studies that measure the relationships between workload and these variables in the post-COVID-19 era.ObjectiveTo evaluate the effect of workload on quiet quitting, turnover intention, and job burnout.MethodsWe conducted a cross-sectional study using a sample of nurses in Greece. The NASA task load index was used to measure workloads among nurses. Also, we used valid scales to measure quiet quitting (quiet quitting scale), job burnout (single item burnout measure), and turnover intention (a six-point Likert scale).ResultsThe mean workload score was 80.7, indicating high workloads in our sample. Moreover, most of the nurses belonged to the group of quiet quitters (74.3%). About half of the nurses reported a high level of turnover intention (50.2%). After controlling for confounders, data analysis showed that higher workloads were associated with higher levels of quiet quitting [beta = 0.009, 95% confidence interval (CI) = 0.006 to 0.012, p-value < 0.001], turnover intention (odds ratio = 1.046, 95% CI = 1.035 to 1.056, p-value < 0.001), and job burnout (beta = 0.072, 95% CI = 0.065 to 0.079, p-value < 0.001).ConclusionWe found that workload was associated with quiet quitting, turnover intention, and job burnout in nurses. Thus, appropriate interventions should be applied to reduce nursing workloads to improve productivity and the healthcare provided to patients.